ปัจจัยที่มีความสัมพันธ์กับการกลับเข้าทำงานของแรงงานสูงอายุที่ประสบอันตรายจากการทำงานในจังหวัดสมุทรปราการ - เพ็ญพิชญา วงษ์วิวัฒน์ (กรมแพทย์ทหารเรือ, 2022)
This report was a retrospective study. The aim of this study was to estimate the associated factors of return to work (RTW) and determine proportion of RTW among older workers (50 - 80 years old) with occupational injuries in Samut Prakan, Thailand. Secondary data for 433 cases were gathered from workers’ compensation claims from January to December, 2020. Most of the participants had successful RTW within 180 days after injury (99.77%). Median survival time to RTW was 5 days. There was a strong relationship between income, nature of injury, body location of injury and probability of RTW. We found that the highest income group had the least probability of RTW (HRadj = 0.63; 95% CI: 0.45 - 0.89) compared with the lowest income group. Wound, laceration, and amputations injury, as well as head injury had the highest probability of RTW among each group which were 2.78 times (HRadj = 2.78; 95% CI: 1.64 -4 .74) and 2.24 times (HRadj = 2.24; 95% CI: 1.32 - 3.82), respectively. In the adjusted analysis, we found that there was no association between age and RTW. In conclusion, while the severity of injury may play a major role in determining the success of RTW, there is no evidence in this study that suggest age was associated with RTW. Assessment for probability of severe work-related accident, however, is imperative in assigning appropriate job for each.